Ergonomic Design of Women's Clothing for Middle Age: Physical and Emotional Perception - das Neves, Erica Pereira [UNESP]; Cruz Bonfim, Gabriel Henrique; Moreira da Silva, Fernando J. C.; Paschoarelli, Luis C. [UNESP]; Broega, A. C.; Cunha, J.; Carvalho, H.; Providencia, B. (Springer, 2023)
Over the last decades, the fashion industry has been facing the challenge of adapting to the critical power of its users, who are increasingly informed and aware. Concerning the female universe, the physical and emotional aspects resulting from the aging process, specifically the climacteric and menopause stages, influence the perception of clothing, both for its aesthetic characteristics and its usability aspects. In this sense, this investigation aims to identify the perception of middle-aged women concerning their physical variables as well as identify subjective and emotional responses regarding their relationship with fashion, primarily, clothing. The results showed that clothing was considerably associated with redesign and manipulation of the body. This relationship was associated with the construction of the individual's image, as well as their personal and emotional satisfaction, psychological well-being, and pleasure.
Keywords: Ergonomic design; Fashion design; Middle-aged women; fashion perception